2022
DOI: 10.1038/s44161-022-00035-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental venous anomalies are a genetic primer for cerebral cavernous malformations

Abstract: Introductory Paragraph Cerebral cavernous malformations (CCM) are a neurovascular anomaly that may occur sporadically, or be inherited due to autosomal dominant mutations in KRIT1 , CCM2 , or PDCD10 . Individual lesions are caused by somatic mutations which have been identified in KRIT1, CCM2, PDCD10, MAP3K3, and PIK3CA . However, the interactions between mutations, and their relative c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…Collectively, our findings demonstrate a functional redundancy in the ERK1/2 and mTORC1 signaling pathways in regulating endothelial cell proliferation and vessel enlargement and that inhibition of cell growth through ERK1/2 or mTORC1 alone is not sufficient to rescue cytoskeletal perturbations that are regulated by mTORC2/Rac1/PAK signaling. These findings are in line with the two-hit model of CCMs, where loss of function mutations of the CCM complex that result in increased MEKK3–ERK5–Krüeppel-like factor signaling and a subsequent gain of function mutation in PIK3CA signaling synergize to promote aggressive CCM lesions ( 61 , 62 ).…”
Section: Discussionsupporting
confidence: 85%
“…Collectively, our findings demonstrate a functional redundancy in the ERK1/2 and mTORC1 signaling pathways in regulating endothelial cell proliferation and vessel enlargement and that inhibition of cell growth through ERK1/2 or mTORC1 alone is not sufficient to rescue cytoskeletal perturbations that are regulated by mTORC2/Rac1/PAK signaling. These findings are in line with the two-hit model of CCMs, where loss of function mutations of the CCM complex that result in increased MEKK3–ERK5–Krüeppel-like factor signaling and a subsequent gain of function mutation in PIK3CA signaling synergize to promote aggressive CCM lesions ( 61 , 62 ).…”
Section: Discussionsupporting
confidence: 85%
“…Subsequent work has also highlighted the importance of somatic mutation as a genetic agent [3]. A recent study has provided good insights into cerebral cavernous malformations with DVA [2]. However, spinal cord CM with associated DVA is not common, and sequencing analysis of genetic mutations has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…DVAs may have a somatic activating mutation in the PIK3CA gene, leading to a gain of function, which acts as a genetic precursor to a sporadic CCM. 7 An acquired second-hit mutation in the CCM complex (KRIT1, CCM2, PDCD10) or MAP3K3 then results in the formation of a sporadic CCM, 7 supported by the observation that sporadic CCMs often develop within the venous drainage territory of the DVA. 8 On the other hand, hereditary CCMs preferentially develop via a mutation in the CCM complex (CCM1, CCM2, CCM3 gene loci) or the MAP3K3 locus, causing multiple quiescent CCMs, which may acquire an additional mutation in PIK3CA, driving lesional growth.…”
Section: Neurovascular and Genetic Pathogenesismentioning
confidence: 99%
“…8 On the other hand, hereditary CCMs preferentially develop via a mutation in the CCM complex (CCM1, CCM2, CCM3 gene loci) or the MAP3K3 locus, causing multiple quiescent CCMs, which may acquire an additional mutation in PIK3CA, driving lesional growth. 7 Symptomatic DVA Symptomatic DVA is an umbrella term that encompasses a diverse range of DVA-related complications. Systematic review predominately from low-level evidence (ie, case series or casecontrol studies) showed that an astounding 61% of DVAs are asymptomatic: 23% with nonspecific clinical presentation, 6% with a focal neurologic deficit, 6% with hemorrhage, 4% with seizures, and ,1% with infarct.…”
Section: Neurovascular and Genetic Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation